An Efficient Photocatalytic Degradation of Methyl Blue Dye by using Synthesised PbO Nanoparticles - Ashok V. Borhade; Dipak R. Tope; Bhagwat K. Uphade (E-Journal of Chemistry)
We report here the synthesis of visible light sensitive PbO and Ni doped PbO nanoparticles by hydrothermal method and characterized by UV-DRS, photoluminescence spectroscopy (PL), FTIR, X-ray diffraction (XRD), SEM, EDAX and TGA. Further an efficient approach has been developed for degradation of methyl blue (MB) in aqueous medium. The photodegradation of dye was monitored as a function of dye concentration, pH and catalyst amount has been determined. The reduction in the chemical oxygen demand (COD) revealed the mineralization of dye along with colour removal.